2001
DOI: 10.1002/1097-4636(200111)57:2<200::aid-jbm1159>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of cultured smooth muscle cells by corrosion products of 316 L stainless steel wire

Abstract: The potential cytotoxicity on vascular smooth muscle cells of corrosion products from 316 L stainless steel, one of most popular biomaterials of intravascular stents, has not been highlighted. In this investigation, 316 L stainless steel wires were corroded in Dulbecco's modified eagle's medium with applied constant electrochemical breakdown voltage, and the supernatant and precipitates of corrosion products were prepared as culture media. The effects of different concentrations of corrosion products on the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…CAD models of Palmaz-Schatz stents (SS stent) with different values of metal-to-artery ratio expansion, lower bending stresses when deployed in tortuous vessels and the elimination, after balloon deflation, of high radial dimension reduction due to the stent elastic deformation recovery (Carter et al 1998). Moreover, SMA, and in particular NiTi alloys, seem to have a better biocompatibility and corrosion resistance than AISI 316L (Trepanier 1999;Shih 2001;Thierry 2002). Some clinical studies (Han et al 2001;Kobayashi et al 2001;Taylor et al 2001, Virmani 2002 compare NiTi alloy and stainless steel stent performance suggesting that NiTi stents, designed to allow continued expansion of the stent, induce positive remodeling of the artery, favor the long-term lumen patency and reduce the restenosis.…”
Section: Application To a New Generation Self-expandable Stentmentioning
confidence: 99%
“…CAD models of Palmaz-Schatz stents (SS stent) with different values of metal-to-artery ratio expansion, lower bending stresses when deployed in tortuous vessels and the elimination, after balloon deflation, of high radial dimension reduction due to the stent elastic deformation recovery (Carter et al 1998). Moreover, SMA, and in particular NiTi alloys, seem to have a better biocompatibility and corrosion resistance than AISI 316L (Trepanier 1999;Shih 2001;Thierry 2002). Some clinical studies (Han et al 2001;Kobayashi et al 2001;Taylor et al 2001, Virmani 2002 compare NiTi alloy and stainless steel stent performance suggesting that NiTi stents, designed to allow continued expansion of the stent, induce positive remodeling of the artery, favor the long-term lumen patency and reduce the restenosis.…”
Section: Application To a New Generation Self-expandable Stentmentioning
confidence: 99%
“…The corrosion of 316L-SS stents causes the release of cytotoxic constituents such as nickel and chromium ions [50,51]. It was previously shown that these potentially toxic compounds are stocked in the tissues surrounding the stent and can migrate through the blood, to be accumulated in vital organs such as kidney, spleen and liver [2,[52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown that these potentially toxic compounds are stocked in the tissues surrounding the stent and can migrate through the blood, to be accumulated in vital organs such as kidney, spleen and liver [2,[52][53][54]. In addition, Shih et al reported that the corrosion products can even alter the rat aortic SMC morphology [50].…”
Section: Introductionmentioning
confidence: 99%
“…Ion release potentially provides proinflammatory, cytotoxic or fibro-proliferative stimuli. Furthermore, allergenic, carcinogenic or toxic effects, especially of nickel ions, have been frequently discussed [9,[34][35][36]. Corrosion has furthermore been described as a contributor to stent fracture in the periphery [37].…”
Section: Discussionmentioning
confidence: 99%